Natural Decay Resistance of Indian Timbers-v. Decay Resistance of Haldu (Adina cordifolia Hook.f.), Salai (Boswellia serrata Roxb), Walnut (Juglans regia Linn.), Mango (Mangifera Indica Linn.) and Bahera (Terminalia bellirica Roxb.) - Puri, Y. N.; Singh, Sujan; Khan, S. N.; Bakshi, B. K. (Indian Forester, 1968)
Results of studies on the natural decay resistance of 5 hardwood timber species, viz., haldu (Adina cordifolia Hook. F.), salai (Boswellia serrata Roxb.), mango (Mangifera indica Linn.), walnut (Juglans regia Linn.) and bahera Terminalia bellirica Roxb.) are reported. In all the species, except walnut, true heartwood is absent or formed only rarely. All are non-resistant against wood-rotting fungi. These findings based on laboratory tests correspond closely with the performance of the species in ’grave-yard’ tests.